Ética em Turismo - Wyse, Nely (Boletim Técnico do Senac, 2006)
This article deals with the theme “Vocational training for tourism” from the perspective of ethics in postmodern society. Based on an analysis of the three vocational training principles for tourism established by the new curricular parameters set by the Ministry of Education and Culture (MEC) – aesthetics of sensibility, identity ethics, and equality policy–aligned to the virtues of prudence, temperance, courage, and justice, the points of convergence between ethics and the so-called “sustainable tourism” are set. The proposal recognizes the intrinsic interdisciplinary character of the tourism sector, acknowledging that tourism is part of the Human Sciences and therefore it is subjected to societies’ paradigm shifts. This approach aims to exclude reductionist views that intend to segment the phenomenon of tourism, thus losing sight of what is intrinsic to it – its complexity.